SOURCES OF FORMATION OF ASSETS AND THEIR ROLE IN STABILIZATION OF A SUSTAINABLE DEVELOPMENT OF ECONOMIC ENTITIES OF THE KYRGYZ REPUBLIC - Mаrina V. Shtiller (Статистика и экономика)
In article questions of research of economic essence and the maintenance of sources of formation of assets and their role in stabilization of a sustainable development of the enterprises of the Kyrgyz Republic are considered. The main characteristics inherent in the capital of an economic entity are dened.